Formulasi dan Uji Stabilitas Hair Tonic Ekstrak Lidah Buaya (Aloe vera L.) dan Seledri (Apium graviolens L.) - Indriyani, Fajar; Endrawati-Politeknik Kesehatan Bhakti Mulia, Susi (IJMS - Indonesian Journal on Medical Science, 2021)
Abstract : Aloe vera contains vitamins A, C, amino acids, Cu, Inositol, enzymes, minerals that can help reduce hair loss and strengthen hair roots. While celery contains sodium, vitamins A and B, calcium and iron which have the potential to nourish hair, black hair, and prevent hair loss. To prove that the combination of aloe vera extract (Aloe vera L.) and celery extract (Apium graviolens L.) can be formulated in hair tonic preparations, and determine the formula that best meets the stability requirements of the 1 month observation. This study is an experimental study by formulating and testing the stability of hair tonic preparations. The results of the viscosity and specific gravity tests were analyzed using ANOVA with software version 22. Organoleptic hair tonic combination of aloe vera and celery extract in the form of a solution with a characteristic aromatic odor, greenish brown color, has a pH of 4, and is homogeneous. The specific gravity of formulas 1, 2 and 3, respectively, is 0.99553 g / ml; 1.00114 g / ml 1.00661 g / ml. The viscosity of formulas 1, 2 and 3, respectively, is 3.96407 cPs; 6,77595 cPs; 11.16378 cPs. ANOVA test shows a significance value (<0.001) <(0.05) so that there are differences in viscosity and specific gravity between formulations. The combination of aloe vera and celery extract can be formulated into a hair tonic and the formula that best meets the stability requirements is formula 1 with a concentration of 15% propylenglycol.Keywords: hair tonic, stability test, aloe vera extract, celery extract Abstrak : Lidah buaya mengandung vitamin A, C, asam amino, Cu, Inositol, enzim, mineral yang dapat membantu mengurangi kerontokan rambut dan menguatkan akar rambut. Sedangkan seledri mengandung natrium, vitamin A dan B, kalsium dan zat besi yang berpotensi untuk menyuburkan rambut, menghitamkan rambut, dan mencegah kerontokan. Membuktikan bahwa kombinasi ekstrak lidah buaya (Aloe vera L.) dan ekstrak seledri (Apium graviolens L.) dapat diformulasikan dalam sediaan hair tonic, dan mengetahui formula yang paling memenuhi persyaratan stabilitas pada pengamatan selama 1 bulan. Penelitian ini merupakan penelitian eksperimental yaitu dengan menformulasikan dan menguji stabilitas sediaan hair tonic. Hasil uji viskositas dan bobot jenis dianalisis menggunakan ANOVA dengan software versi 22. Organoleptis hair tonic kombinasi ekstrak lidah buaya dan seledri berbentuk larutan dengan bau khas aromatik, warna coklat kehijauan, memiliki pH 4, dan bersifat homogen. Bobot jenis formula 1, 2 dan 3 berturut-turut yaitu 0,99553 g/ml ; 1,00114 g/ml 1,00661 g/ml. Viskositas formula 1, 2 dan 3 berturut-turut yaitu 3,96407 cPs; 6,77595 cPs; 11,16378 cPs. Uji ANOVA menunjukkan nilai signifikansi (< 0,001) < (0,05) sehingga ada perbedaan viskositas dan bobot jenis antar formulasi. Kombinasi ekstrak lidah buaya dan seledri dapat diformulasikan menjadi hair tonic serta formula yang paling memenuhi persyaratan stabilitas adalah formula 1 dengan konsentrasi propilenglikol 15%.Kata kunci : hair tonic, uji stabilitas, ekstrak lidah buaya, ekstrak seledri